Moving Beyond Substantive Grounded Theory - Kara L. Vander Linden (Grounded Theory Review: An International Journal)
The grounded theory methodology has been primarily used to develop substantive theories; however, since its inception, the developers of the methodology have encouraged researchers to move beyond substantive grounded theory by developing mid-range and formal grounded theories and applying grounded theories. While still a “neglected option,” this article discusses each of these options and explains how these options all involve the continued collection of data within new areas and new populations, the use of the constant comparative method of analysis to compare indicators within the data, and the modification of the existing theories for fit and relevance. The article concludes by discussing some possible barriers to moving beyond substantive grounded theory. With awareness of these obstacles, we may be better able to address them and increase the development of mid-range and formal grounded theories and the application of grounded theories.